2020
DOI: 10.1109/jstars.2020.2966880
|View full text |Cite
|
Sign up to set email alerts
|

Sea Ice Thickness Measurement Using Spaceborne GNSS-R: First Results With TechDemoSat-1 Data

Abstract: In this article, an effective schematic is developed for estimating sea ice thickness (SIT) from the reflectivity (Γ) produced with TechDemoSat-1 (TDS-1) Global Navigation Satellite System-Reflectometry data. Here, Γ is formulated as the product of the propagation loss due to SIT and the reflection coefficient of underlying seawater. The effect of surface roughness on Γ is neglected when only considering signals of coherent reflection. In practice, Γ at the specular point is first generated using TDS-1 data. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 34 publications
(46 reference statements)
0
24
1
Order By: Relevance
“…During the last decades, Global navigation satellite system reflectometry (GNSS-R) has become a valid option for ocean remote sensing (Garrison and Katzberg, 2000). The feasibilities of the GNSS-R technique for sensing different geophysical parameters, such as ocean wind speed (Clarizia and Ruf, 2016;Ruf and Balasubramaniam, 2018), significant wave height (SWH; Soulat et al, 2004;Roggenbuck et al, 2019), sea ice detection (Alonso- Arroyo et al, 2017;Yan and Huang, 2018), ocean altimetry (Li et al, 2017;Hu et al, 2020;Tabibi et al, 2020), and soil moisture (Alonso Arroyo et al, 2014;Chew and Small, 2018;Yan and Huang, 2020), have been demonstrated with theoretical analyses and massive ground-based, airborne, and spaceborne experiments.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, Global navigation satellite system reflectometry (GNSS-R) has become a valid option for ocean remote sensing (Garrison and Katzberg, 2000). The feasibilities of the GNSS-R technique for sensing different geophysical parameters, such as ocean wind speed (Clarizia and Ruf, 2016;Ruf and Balasubramaniam, 2018), significant wave height (SWH; Soulat et al, 2004;Roggenbuck et al, 2019), sea ice detection (Alonso- Arroyo et al, 2017;Yan and Huang, 2018), ocean altimetry (Li et al, 2017;Hu et al, 2020;Tabibi et al, 2020), and soil moisture (Alonso Arroyo et al, 2014;Chew and Small, 2018;Yan and Huang, 2020), have been demonstrated with theoretical analyses and massive ground-based, airborne, and spaceborne experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of TDS-1 data for sea ice altimetry were explored in a number of previous studies [29][30][31], while the raw data used in [29] and [30] are not in the standard dataset open to the public. Besides the detection of sea ice, GNSS-R has been applied to retrieve sea ice parameters, such as sea ice type [32], sea ice concentration [33] and sea ice thickness [34].…”
Section: Introductionmentioning
confidence: 99%
“…Data quality is also affected by incident angle, antenna gain, and satellite attitude. After denoising the DDM data, we calculated the RMS values of DDW, as shown in Equation (13). We selected good-quality DDM data by adjusting the root mean square (RMS) threshold of cleaned DDW.…”
Section: Methodsmentioning
confidence: 99%